Enhanced chemosensory sensitivity in patients with idiopathic rhinitis and its reversal by nasal capsaicin treatment - Van Gerven, Laura; Alpizar, Yeranddy A.; Steelant, Brecht; Callebaut, Ina; Kortekaas Krohn, Inge; Wouters, Mira; Vermeulen, François; Boeckxstaens, Guy; Talavera, Karel; Hellings, Peter W. (Journal of allergy and clinical immunology, 2017)
The therapeutic action of capsaicin treatment in patients with idiopathic rhinitis (IR) is based on ablation of the transient receptor potential cation channel subfamily V, receptor 1 (TRPV1)–substance P nociceptive signaling pathway. However, the functional consequences of capsaicin treatment on nasal nerve activation and the association between the reduction in nasal hyperreactivity (NHR) and response to capsaicin treatment remain unknown. We sought to study the effects of capsaicin nasal spray on the afferent innervation of the nasal mucosa by monitoring trigeminal nerve activity in patients with IR and healthy control (HC) subjects. A double-blind, placebo-controlled randomized trial with capsaicin nasal spray was performed involving 33 patients with IR and 12 HC subjects. Before and at 4, 12, and 26 weeks after treatment, nasal mucosal potentials (NMPs) were measured while exposing the nasal mucosa of patients with IR and HC subjects to aerosols with increasing doses of the chemical irritants allyl isothiocyanate (AITC; also known as mustard oil) or capsaicin. The threshold for each compound was determined for each subject. The results of the NMP measurements were evaluated in parallel with the therapeutic response, visual analog scale scores for nasal symptoms, self-reported NHR, and mRNA expression of PGP9.5; TRPV1; transient receptor potential cation channel subfamily A, receptor 1 (TRPA1); TRPV4; transient receptor potential cation channel subfamily M, member 8 (TRPM8); and nerve growth factor (NGF) in nasal biopsy specimens. AITC turned out to be the best stimulus because the coughing induced by capsaicin interfered with measurements. At baseline, the threshold for evoking changes in NMPs based on AITC was significantly lower for patients with IR compared with HC subjects (P = .0423). Capsaicin treatment of IR patients increased the threshold for the response to AITC at 4 and 12 weeks compared with placebo (P = .0406 and P = .0325, respectively), which returned to baseline by week 26 (P = .0611). This increase correlated with changes in visual analog scale major symptom (P = .0004) and total symptom (P = .0018) scores. IR patients with self-reported NHR at baseline showed a trend to being better responders to capsaicin treatment compared with patients with IR but without NHR (P = .10). The lower threshold for AITC based on NMPs in patients with IR compared with HC subjects and the increased threshold for AITC after capsaicin treatment in patients with IR demonstrate the crucial role of TRPA1 and TRPV1 in IR pathophysiology. The strong correlation between the increase in AITC threshold in patients with IR and symptom reduction after capsaicin treatment demonstrates the clinical relevance of these findings.